BLOOD PRESSURE SCREENING THROUGH FREE HEALTH SERVICE PROGRAM IN AMAHAMI, BIMA CITY, NTB - Noris, Muhammad; Firmansyah, Muh.; Darmin, Darmin; Iksan, Muammar; Husnul Khatimah, Nur; Zara Avila, Dea (Journal of Excellence Humanities and Religiosity, 2024)
Blood pressure is one of the most commonly measured clinical parameters. One of the preventive steps that data takes is to carry out free checks. This activity is an implementation of the tri dharma of higher education in the form of community service carried out by the nutrition study program, faculty of health, Bima Muhammadiyah University. The aim of the activity is to diagnose and detect early health symptoms in people's blood pressure to ensure superior human resources and Sustainable Development Goals (SDGs). The Free Examination Activity was attended by 55 people. The activity method consists of 3 stages including the preparation stage, data collection stage, inspection stage and consultation. The hope is that with a program like this, it can reduce and minimize the risk of blood pressure disorders in the people of Bima City. It is hoped that programs like this can reduce and minimize the risk of blood pressure disorders in the people of Bima City, the formation of healthy living behaviors, and the fulfillment of balanced nutrition that encourages the quality of superior human resources.